Pengaruh Budaya Terhadap Perkembangan Sastra Lisan - Dharmojo Dharmojo (Balai Bahasa Provinsi Papua, 2019)
Foklore is part of oral tradition have positive values and deserving of preserved, developed, and utilized to supporting society life. Besides, folklore still scattered in verbal type that function as reveal nature thoughts, attitude, and supporting culture values, on eventually towards new culture forming wider. Folklore included cover (1) people language (folk speech), as patois, epithet, traditional position, and nobility title; (2) traditional expressions, as proverb, adage, and pameo; (3) traditional questions, as puzzle; (4) people poems, as poetry, poe, and poem; (5) prose stories, as mite, legend, myth; and (6) folk songs.